Standardization of a method of prolonged thoracic surgery and mechanical ventilation in rats to evaluate local and systemic inflammation - Leite,Camila Ferreira (2011)
Purpose: To evaluate the immediate pulmonary and systemic inflammatory response after a long-term operative period. Methods: Wistar rats in the experimental group were anaesthetized and submitted to tracheostomy, thoracotomy and remained on mechanical ventilation during three hours. Control animals were not submitted to the operative protocol. The following parameters have been evaluated: pulmonary myeloperoxidase activity, pulmonary serum protein extravasation, lung wet/dry weight ratio and measurement of levels of cytokines in serum. Results: Operated animals exhibited significantly lower serum protein extravasation in lungs compared with control animals. The lung wet/dry weight ratio and myeloperoxidase activity did not differ between groups. Serum cytokines IL-1ß, TNF-, and IL-10 levels were not detected in groups, whereas IL-6 was detected only in operated animals. Conclusion: The experimental mechanical ventilation in rats with a prolonged surgical time did not produce significant local and systemic inflammatory changes and permit to evaluate others procedures in thoracic surgery.